Ennis Franciscan Friary, eastern tomb niche, north nave wall, jamb and arch moulding - O'Donovan, Danielle (My University, 2008)
Jamb and arch of tomb niche. From intrados moulding comprises: ogee, quadrant. Similar tomb niches can be found at Quin, Adare Franciscan, Adare Augustinian, Askeaton, Lislaughtin, Abbeydorney, Kilconnell.
Tomb niche
Keywords: quadrant; Architecture, Gothic -- Ireland; Ennis (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Funerary monuments; Late Medieval; moldings, ogee; roll moldings